2003
DOI: 10.1124/dmd.31.11.1419
|View full text |Cite
|
Sign up to set email alerts
|

PHARMACOKINETICS OF A TUMOR NECROSIS FACTOR-α PHOSPHOROTHIOATE 2′-O-(2-METHOXYETHYL) MODIFIED ANTISENSE OLIGONUCLEOTIDE: COMPARISON ACROSS SPECIES

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:The pharmacokinetics of a 2-O-(2-methoxyethyl)-ribose modified phosphorothioate oligonucleotide, ISIS 104838 (human tumor necrosis factor-␣ antisense), have been characterized in mouse, rat, dog, monkey, and human. Plasma pharmacokinetics after i.v. administration exhibited relatively rapid distribution from plasma to tissues with a distribution half-life estimated from approximately 15 to 45 min in all species. Absorption after s.c. inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
128
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 21 publications
8
128
0
Order By: Relevance
“…In that study, therapeutic success was aided by the fact that antisense compounds reach high concentrations in the liver, where virtually all of the apoB100 and LDL cholesterol originate. In the case of the progeria, the antisense reagents would probably need to reduce prelamin A levels in bone, muscle, and fat - tissues where the concentrations of oligonucleotide tend to be lower (30). However, even if oligonucleotide concentrations in these tissues were relatively low, it is still conceivable that disease phenotypes could be partially ameliorated.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In that study, therapeutic success was aided by the fact that antisense compounds reach high concentrations in the liver, where virtually all of the apoB100 and LDL cholesterol originate. In the case of the progeria, the antisense reagents would probably need to reduce prelamin A levels in bone, muscle, and fat - tissues where the concentrations of oligonucleotide tend to be lower (30). However, even if oligonucleotide concentrations in these tissues were relatively low, it is still conceivable that disease phenotypes could be partially ameliorated.…”
Section: Figurementioning
confidence: 99%
“…We are cautiously optimistic that ISIS 359445 might be effective in vivo. One reason for optimism is that chimeric phosphorothioate oligodeoxynucleotides containing 2′-O-methoxyethyl (2′-MOE) modifications are extremely resistant to nucleases, have long half-lives (up to a week in mice), and support the RNAse H-mediated removal of the target transcript (29,30). Oligonucleotides specific for mouse (or human) apoB (employing the same chemistry) have previously been found to be very effective, lowering the levels of both apoB100 and LDL cholesterol in the plasma (31).…”
Section: Figurementioning
confidence: 99%
“…NAPs may be of therapeutic benefit to treat many viral infections, as NAPs share the well-conserved pharmacokinetic characteristics of PS-ONs in mammalian species: following administration, PS-ONs are rapidly cleared from the blood (typically less than 1 h), with significant and durable accumulations in the kidney, liver, spleen, and lung (levels of accumulation are greatest in the kidney, with decreasing but still significant amounts in liver, spleen, and lung), and up to 40% of the administered dose accumulates in the liver (13)(14)(15)(16). Consistent with this behavior, NAPs have been shown to be active in vivo against virus infections with tropism in these organs: CMV, HCV, LCMV, influenza virus A, and respiratory syncytial virus (RSV) (7, 10, 11; A. Vaillant, unpublished observation).…”
mentioning
confidence: 99%
“…By comparing hundreds of ASOs that target various splicing silencers in exon 7 and both flanking introns (Hua et al 2008; data not shown), we identified an optimal 18mer 29-O-(2-methoxyethyl) (MOE) ASO (#10-27) that targets ISS-N1 in intron 7. The lead ASO also promotes efficient SMN2 exon 7 inclusion in the liver and kidneys of transgenic mice after systemic administration, but not in the spinal cord (Hua et al 2008), owing to a lack of distribution across an intact blood-brain barrier (BBB) (Geary et al 2003).…”
mentioning
confidence: 99%